A Finite Points Method Approach for Strain Localization Using the Gradient Plasticity Formulation. (11th December 2014) - Pérez Pozo, Luis; Campos, Andy; Lascano, Sheila; Oller, Sergio; Rodríguez-Ferran, Antonio
Abstract : The softening elastoplastic models present an unsuitable behavior after reaching the yield strength: unbounded strain localization. Because of the material instability, which is reflected in the loss of ellipticity of the governing partial differential equations, the solution depends on the discretization. The present work proposes to solve this dependency using the meshless Finite Points Method. This meshfree spatial discretization technique allows enriching the governing equations using gradient's plasticity and introducing an internal length scale parameter at the material model in order to objectify the solution.